Translation Strategies and Translations of Realia in the Finnish Translation of The Cruel Prince - Liljeqvist, Anna (My University, 2025)
This thesis explores the translation of nomenclature from The Cruel Prince (2018) by Holly Black. The aim of this research was to understand what translation strategies were used and what other effective factors were considered in this translation. The material was collected from the novel The Cruel Prince and from its Finnish translation Julma Prinssi (2024). The material was analysed in the light of Ritva Leppihalme’s translation strategies, Mika Loponen’s definition of irrealia, and Ainiala’s view on translation nomenclature. The results indicated that the translation of the nomenclature used foreignizing and domesticating as the global strategies, and different local strategies according to the needed solution for a certain problem, for example with character names or with place names. While these findings cannot be used to generalize the translation process of fantasy literature, they give an idea of what types of solutions are possible to use when translating fantasy.
Keywords: translation, translation strategies, fantasy literature, realia, irrealia, nomenclature, young adult literature